Cyclin‐dependent kinase 4 inhibits the translational repressor 4E‐BP1 to promote cap‐dependent translation during mitosis–G1 transition. Issue 8 (31st December 2019) - Mitchell, Dylan C.; Menon, Arya; Garner, Amanda L.
Abstract : Phosphorylation of translational repressor eukaryotic translation initiation factor 4E (eIF4E)‐binding protein 1 (4E‐BP1) controls the initiation of cap‐dependent translation, a type of protein synthesis that is frequently upregulated in human diseases such as cancer. Because of its critical cellular function, it is not surprising that multiple kinases can post‐translationally modify 4E‐BP1 to drive aberrant cap‐dependent translation. We recently reported a site‐selective chemoproteomic method for uncovering kinase–substrate interactions, and using this approach, we discovered the cyclin‐dependent kinase (CDK)4 as a new 4E‐BP1 kinase. Herein, we describe our extension of this work and reveal the role of CDK4 in modulating 4E‐BP1 activity in the transition from mitosis to G1, thereby demonstrating a novel role for this kinase in cell cycle regulation. Abstract :